Divinatory Logics Diagnoses and Predictions Mediating Outcomes - Zeitlyn, D (University of Chicago Press, 2012)
This paper is about the logics of how practitioners and their clients use divination in their ongoing involvement with everyday life. It asks philosophical questions of the implications of praxis and suggests that the answers are not always what philosophers might expect. I distinguish two uses or aspects of divinatory usage: that concerned with the present or past, diagnosis, and that concerned with the future, prognosis or prediction. Divinatory practice often contains both aspects; however, the distinction helps our understanding of how divination is used. Examples are taken from Evans-Pritchard on Zande divination (oracles) and from my ongoing work on Mambila spider divination. Some parallels are drawn with ambiguities in financial measures and the ways in which they are used to justify decisions about the systems they "measure." Social predictions similarly move between styles of usage (exemplified by Merton's self-fulfilling prophecy). The idea of divinatory logics moves us from the sphere of philosophy to a less rigorously defined sphere of social interaction, where what counts as success may be that we have changed the world so that a statement of fact does not obtain. In a world of counterfactual conditionals, the diviner, not the philosopher, is king. © 2012 by The Wenner-Gren Foundation for Anthropological Research. All rights reserved.